Perspective on Pulsed Electric Field Treatment in the Bio-based Industry - Buchmann, Leandro; Mathys, Alexander (Frontiers in Bioengineering and Biotechnology, 2019)
The bio-based industry is urged to find solutions to meet the demands of a growing world population. In this context, increased resource efficiency is a major goal. Pulsed electric field (PEF) processing is a promising technological solution. Conventional PEF and the emerging area of nanosecond PEF (nsPEF) have been shown to induce various biological effects, with nsPEF inducing pronounced intracellular effects, which could provide solutions for currently faced challenges. Based on the flexibility and continuous operation of PEF and nsPEF processing, the system can be integrated into any existing cultivation system; its modularity provides an approach for inducing specific effects. Depending on the treatment conditions, selective inactivation, continuous extraction without impeding cell viability, as well as the stimulation of cell growth or cellular compound stimulation are potential applications in the bio-based industry. However, continuous treatment currently involves heterogeneous energy inputs. Increasing the homogeneity of PEF and nsPEF processing by considering the flow and electric field heterogeneity may allow for more targeted effects on biological cells, further increasing the potential of the technology for bio-based applications. We provide an overview of existing and potential applications of PEF and nsPEF and suggest that theoretical and practical analyses of flow and electric field heterogeneity may provide a basis for obtaining more targeted effects on biological cells and for further increasing the bio-based applications of the technology, which thereby could become a key technology for circular economy approaches in the future.